MEDICO-LEGAL EVALUATION OF CAUSES OF SUDDEN DEATH DUE TO CARDIOVASCULAR DISEASES AND THEIR SURVIVAL TIME (Journal of Forensic Medicine & Toxicology, 2025)
The world health organization defines sudden death as a death which occurs within 24 hours from the onset of symptoms. The diseases of the cardiovascular system contributes to one of the most important causes of sudden death in medico-legal autopsies. Cardiovascular diseases are the number one cause of death globally, more people die annually from cardiovascular diseases than from any other cause. We examined 189 cases of sudden deaths in which 104 deaths (55% ) were due to cardiovascular diseases. Amongst cardiovascular system, the diseases which caused the sudden death were coronary artery disease in 77 cases (41%), myocardial infarction in 18 cases (10%) and cardiac tamponade in 9 cases (5%) of all 189 cases of sudden death. We also observed mean survival time was 4 hours and 30 minutes in sudden deaths due to cardiovascular diseases.
Keywords: Cardiovascular diseases; sudden death; survival time